A case report of severe drug-induced immune hemolytic anemia caused by piperacillin - Zhao, Hong (Frontiers in Immunology, 2024)
Piperacillin is a beta-lactamase inhibitor frequently used in the treatment of urinary tract infections. It is a broad-spectrum antibiotic with strong antibacterial action against Pseudomonas aeruginosa and Enterobacter, especially extended-spectrum beta-lactamase-producing Enterobacteria and Enterococcus. Side effects of piperacillin include allergic reactions, rashes such as urticaria, leukopenia, interstitial nephritis, asthma attacks, serological reactions, candida infection, and bleeding with more severe reactions resulting in anaphylactic shock. Anemia and hemolytic anemia are rare adverse reactions to piperacillin, with an incidence of 0.01–0.10%. We report herein the case of a severe postoperative immune hemolytic reaction to piperacillin. Fortunately, we quickly recognized and identified the drug reaction caused by piperacillin, immediately stopped the use of piperacillin, and performed a blood transfusion. The patient recovered and was subsequently discharged from the hospital.